A beam model for the fracture of adhesive joints with dissimilar metal adherends. (April 2022) - de Morais, A.B.
Abstract: The natural ability to join different materials is one of the main advantages of adhesive joints. It is thus important to characterize the fracture resistance of adhesive joints with dissimilar materials, as they are increasingly used in relevant industrial applications. There are, however, well-known problems in data analysis of such tests, especially where mode partitioning is concerned. A beam model is here developed for mixed-mode I-II fracture testing on adhesive joints with dissimilar metal adherends. The model predicts quite accurately the strain-energy release rate, the mode-mix and the load-point displacements with fully closed-form equations. Therefore, it can be the basis of future data reduction schemes for fracture tests. Furthermore, it is shown that a wide range of mode-mix combinations can be achieved with simple well-known tests on dissimilar metal adherend joints. They could thus be an interesting alternative to developed mixed-mode I-II tests that require complex test fixtures.